Genetic divergence of rice genotypes resistant to bacterial blight revealed by quantitative traits and molecular markers - Mazid, Muhammad Sirajul (2013)
Globally, bacterial blight (BB) (Xanthomonas oryzae pv oryzae) of rice is one of the major diseases that impedes rice production to large extent. The strategy of utilizing BB resistant major genes, solely or in combination, continues to be the most fruitful way for controlling this disease. Genetic diversity plays pivotal role in crop improvement. Molecular markers along with quantitative traits have shown their efficacy in the assessment of genetic diversity. Information regarding genetic diversity among the BB resistant genotypes is currently not available adequately in Malaysia. Forty-one rice genotypes obtained from International Rice Research Institute (IRRI), Malaysian Agricultural Research and Development Institute (MARDI) and Bangladesh Rice Research Institute (BRRI) were evaluated at Field 2, Universiti Putra Malaysia. The aims of this study were to determine genetic diversity as well as selection of best genotypes using morphological, physiological traits, and simple sequence repeats (SSR) and inter simple sequence repeats (ISSR) markers. In this study, significant variation was observed among the genotypes for growth, physiological and yield traits. It was also found in the present study, that yield per hill, total number of spikelets per panicle and number of filled grains per panicle had high heritability and genetic advance which are regarded as important for trait selection by the scientists. Cluster analyses based on morphological and physiological traits grouped 41 rice genotypes into six and seven groups respectively. The first four principal components (PCs) from principal component analysis (PCA) based on morphological traits showed 70.80% of total variation while the first three PCs showed 66.60% based on physiological traits. The genetic diversity of the 41 rice genotypes was evaluated with 26 SSR and 20 ISSR markers. A total of 88 alleles and 310 polymorphic loci were detected across the 26 SSR markers and 20 ISSR markers respectively. Cluster analysis based on SSR markers and ISSR markers divided 41 rice genotypes into seven and 11 groups respectively including several sub-clusters. First three PCA from SSR analysis indicated 70.99% of total variation while 37.28% of total variation was found from ISSR analysis. Analysis of molecular variance from SSR analysis expressed 67% variation within populations on the contrary, it was 84% from ISSR markers analysis. The Mantel test revealed positive correlation between quantitative traits and molecular markers. The results of the present study recommended some genotypes for future breeding based on quantitative traits, and SSR and ISSR markers analyses. It is expected that the genotypic combinations could produce bacterial blight resistant and high yielding genotypes. The recommended genotypes for crossing are as follows: MR185 with IRBB5, MR185 with BR28, IRBB4 with Bahagia, MR253 with MR185, MR232 with Purbachi and MR185 with MR232.